A River Runs Through It:: Churchill Falls and the End of Newfoundland History - Bannister, Jerry (Acadiensis)

(untitled) (The Department of History at the University of New Brunswick, 2012)
“Present and Past”: With this issue of Acadiensis, we present to readers a new occasional series entitled “Present and Past.” An outgrowth from the journal’s “Forum” series (which will continue to exist, focusing on debates and complementary perspectives offered by groups of scholars), “Present and Past” will provide regional historians and scholars in related disciplines with the opportunity to reflect on current issues in historical perspective. The principle that scholarly insight can deepen our understanding of contemporary affairs is nothing new in the pages of Acadiensis, as exemplified by the work of many of the journal’s authors. The new series will seek to make this connection more explicit.